Phase Change Materials in Metal Casting Processes: A Critical Review and Future Possibilities - Utkarsh Chadha; Senthil Kumaran Selvaraj; Harshita Pant; Anisha Arora; Divyanshi Shukla; Ishika Sancheti; Arisha Chadha; Divyansh Srivastava; Mayank Khanna; S. Ram Kishore; Velmurugan Paramasivam (Advances in Materials Science and Engineering)
Phase change materials are the category of materials that release or absorb enough energy during phase change transformation to provide heating or cooling. Divided into two principal classes of organic and inorganic, these materials find a wide range of uses in commercial applications of casting where stable temperature and heat storage are a requirement. In this research work, application of inorganic phase change materials having significantly elevated temperature zone, especially within metal casting processes, has been discussed. Phase change material with high enthalpy of fusion and high melting point can be used for metal casting, but in a limited temperature range (between 200°C and 1300°C). In sand casting, inorganic PCM has the potential to be used as chills to provide directional solidification. Despite having advantages, inorganic PCM comes with major disadvantages, that is, toxicity, corrosivity, supercooling, and low thermal expansion. Few solutions to overcome these problems have been discussed in this research paper. Future research is required to reduce the disadvantage to a low level, so that PCM can be used in application where elevated temperature is achieved.